PENGARUH MODEL PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR SISWA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Khairina Safitri; Jesi Alexander Alim; Zetra Hainul Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is often considered a frightening and difficult subject for students. This is one of the causes of reduced student interest in learning mathematics. Based on field observations, the teaching and learning process still uses conventional learning methods, so that learning becomes boring and tends to be monotonous for students and reduces student interest and motivation in learning mathematics material. This study aims to determine the effect of the application of the project based learning (PjBL) method on the learning motivation of second-grade students of SD 177 Pekanbaru. The research method used in this study is an experimental method (pre-experimental design) using a one-group pretest posttest design. The data collection technique used is a questionnaire. Furthermore, researchers use the N-Gain test as a data analysis technique with the help of the IBM SPSS Statistics 29 software program. Based on data analysis, the results obtained are 0.001 <0.05, this can be interpreted that H0 and H1 are rejected. And the results of the N-Gain Score test are 0.56 and the N-Gain percentage is 56%, which means that the interpretation category has a high effectiveness value. So it can be concluded that project-based learning (PjBL) has an effect on the learning motivation of class II students of SD 177 Pekanbaru, namely 56%.